غرائب القرآن میں اشعار عرب سے استشہاد (سیرت ِ ابنِ ہشام کا خصوصی مطالعہ) - Naz, Humaira; Rizvi, Dr. Khurshid (Al-Irfan, 2022)
Strange science and its importance in understanding the meanings of the Quran” deals with the importance authenticity and authority of old words called: “Ilm Gharaib-ul-Quran’’ or “Mufrada tul Quran’’ to understand the meanings of the Holy Quran. This is one of the most important scenic of the Quranic sciences. Poetry was the charisma of Arabs.it was the major part of their temperament and nature.it was the reason they called themselves Afsah ul Lisan(the most eloquent).keeping in view this eminence, the rules and principles of language were defined and prescribed. To understand the holy Quran,the Arabic literature specifically Arabic poetry proved to be useful in all ages. Like the interpreters, the biographers also resorted to the Kalam ul Arab(Arabic language)to understand the meaning of the Holy Quran Ibn e Hisham in his book “Al Seerat un Nabawiyya”(the biography of the Prophet),presented the biographical features with the help of Arabic poetry. He also referred to the Arabic poetry to explain the Gharaib۔ ul۔ Quran of the relevant chapters (Suras) in the context of various matters of Prophet`s life. This paper is an attempt to highlight contribution of Ibn .e.Hisham who has presented different poets as an evident to express diverse notions and concepts.